Field evaluation of PCR in detecting Theileria annulata infection in cattle in eastern Turkey - Aktas, M; Dumanli, N; Çetinkaya, B; Çakmak, A (British Veterinary Assoc, 2002)
[Abstract Not Available]
Keywords: Ticks